MEMORANDUM OF TNEU RESEARCH TEAM ON OVERCOMING THE ECONOMIC CRISIS IN UKRAINE - Yuriy, Serhiy; Dzyublyuk, Oleksandr; Kyrylenko, Olha; Krysovatyy, Andriy; Melnyk, Alla; Savelyev, Yevhen; Sokhatska, Olena (Journal of European Economy, 2017)
.